Effects of antioxidants on viability, plasma membrane integrity and apoptosis in porcine ovarian granulosa cells damaged by bromopropane - Seunghyung Lee; Hee-Woo Park; Sang-Hee Lee; Hee-Tae Cheong; Choon-Keun Park; Boo-Keun Yang (Journal of Animal Reproduction and Biotechnology, 2016)
The purpose of this study was to examine the effects of taurine and vitamin E on ovarian granulosa cells damaged by bromopropane (BP) in pigs. We evaluated cell viability, plasma membrane integrity (PMI) and apoptotic morphological change in porcine ovarian granulosa cells. The cells were treated with 1-BP (0, 5.0, 10, and 50 μM), 2-BP (0, 5.0, 10, and 50 mM), taurine (0, 5.0, 10, and 25 mM), and vitamin E (0, 100, 200, and 400 μM) for 24 h. 10 μM 1-BP and 50 μM 2-BP inhibited viability and PMI, and induced apoptosis in porcine ovarian granulosa cells (p < 0.05). Cell viability and PMI were increased by taurine (10 and 25 mM) and vitamin E (100 and 200 μM), and apoptosis decreased (p < 0.05). Finally, the porcine ovarian granulosa cells were co-treated with BPs (10 μM), taurine (10 mM) and/or vitamin E (200 μM). Cell viability and PMI in the co-treated cells were increased, and apoptosis was decreased. In conclusion, taurine and vitamin E can improve cell viability and inhibition of apoptosis in porcine ovarian granulosa cells damaged by bromopropane.